Comparison of the Ultimate Strength with and without Hatch Opening Subjected to Longitudinal Bending - Indah Melati Suci; Muhammad Zubair Muis Alie; Ganding Sitepu (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
The hatch opening has function to enter the load into the cargo hold. One of the ship types like this is Bulk Carrier. The hatch opening must be designed in suitable way because its influence to the ultimate strength since the hull girder under longitudinal bending moment. The application of the hatch opening on the ship’s deck should be considered for the ship design criteria. The objective of the present study is to analyze the ultimate strength with and without hatch opening subjected to longitudinal bending moment. The cross section of box girder is used to analyze the effect of hatch opening to the ultimate strength. This cross section of box girder is adopted for simple calculation. The application of Multiple Point Constrained (MPC) is adopted to analyze the box girder under longitudinal bending moment. The cross section of box girder is assumed remained plane during progressive collapse. The material such as density, yield strength, elastic modulus and poison ratio are homogeneous. The type and dimensions of the stiffeners are also identic. The only one of the differences for the stiffener is number due to the hatch opening at the top of the box girder. It is found that the ultimate strength of the box girder with hatch opening is smaller than without opening one.